The business of UX writing - Ben-David, Yael (A Book Apart, 2022)
UX writing is good for business, while also playing a critical role in delivering a top-notch user experience. Standing at this pivotal intersection between business goals and user needs is an awesome place to be-as long as we have the mindset, tools, and collaborators to make the most of it. Through case studies, frameworks, and historical context, Yael Ben-David offers savvy and practical guidance to ensure our digital products support the user and the business-plus writers and designers!-all at once.
Includes bibliographical references and index
Keywords: Web sites -- Design; User interfaces (Computer systems) -- Design; Sites Web; Conception; User interfaces (Computer systems); Design; Web sites; Design